1990
DOI: 10.1002/jlb.48.6.495
|View full text |Cite
|
Sign up to set email alerts
|

Avian Inflammatory Macrophage Function: Shifts in Arachidonic Acid Metabolism, Respiratory Burst, and Cell-Surface Phenotype During the Response to Sephadex

Abstract: The avian inflammatory response to intraperitoneal (i.p.) Sephadex injection produces macrophages which display characteristics of an increasingly activated state over time. We examined elicited chicken peritoneal exudate cells (PECs) with respect to superoxide anion production, arachidonic acid metabolism and cell surface Ia and transferrin receptor (TfR) expression from 4 to 96 h after i.p. stimulation. Avian PECs showed the highest level of superoxide release when harvested just 4 h after injection, and did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1992
1992
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…AA infusions trigger rapid increases the PVR and PAP without affecting the cardiac output (Wideman et al, 2005a), and the TxA 2 mimetic U44069 is an extremely potent vasoconstrictor in broilers (Wideman et al, 1999(Wideman et al, , 2005aChapman and Wideman, 2006b). Activated chicken macrophages transiently increase their production of TxA 2 (Golemboski et al, 1990). We reasoned that a pharmacologic blockade of COX-1 and COX-2 sufficient to eliminate the PH caused by an i.v.…”
Section: Introductionmentioning
confidence: 98%
“…AA infusions trigger rapid increases the PVR and PAP without affecting the cardiac output (Wideman et al, 2005a), and the TxA 2 mimetic U44069 is an extremely potent vasoconstrictor in broilers (Wideman et al, 1999(Wideman et al, , 2005aChapman and Wideman, 2006b). Activated chicken macrophages transiently increase their production of TxA 2 (Golemboski et al, 1990). We reasoned that a pharmacologic blockade of COX-1 and COX-2 sufficient to eliminate the PH caused by an i.v.…”
Section: Introductionmentioning
confidence: 98%
“…Monocytes-macrophages kill internalized pathogens mainly by secreting either reactive ROI (primarily H 2 O 2 and O 2 ; Golemboski et al, 1990) and RNI (derived from NO; Sung et al, 1991;Qureshi et al, 1993), both of which play important roles in resisting Salmonella infection (Raupach and Kaufmann, 2001;Withanage et al, 2005). To understand the mechanism of differences in killing ability of monocytes-macrophages to Salmonella Pullorum induced by methyltestosterone, ROI and RNI output was measured, and the results suggested that only ROI contributed to the differences.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we found that active monocytes surround, adhere, and clump on the positively charged beads in vitro [18,29], but not on the neutral or negatively charged beads. The beads may activate macrophages [18,30] and activated tissue macrophages release growth factors and active cytokines into the wound, providing the primary stimulus for the cascade of cell proliferation and matrix deposition that occur during wound healing [2]. Preliminary studies suggested an increase of TGF-␤1 mRNA in the wounds treated with positively charged beads compared to controls at day 7 postwounding.…”
Section: Discussionmentioning
confidence: 99%